Conrad and impressionism - Peters, John G. (John Gerard) (Cambridge : Cambridge University Press, 2001)
John Peters investigates the impact of Impressionism on Conrad and links this to his literary techniques as well as his philosophical and political views. He investigates the sources and implications of Conrad's impressionism in order to argue for a consistent link between his literary technique, philosophical presuppositions and socio-political views.
Cover; Half-title; Title; Copyright; Dedication; Contents; Preface; Acknowledgments; Abbreviations; INTRODUCTION Objects of consciousness in Conrad's impressionist world; CHAPTER 1 Subject/object: science and the epistemological origins of literary impressionism; CHAPTER 2 Objects and events in the primitive eye'': the epistemology of objectivity; CHAPTER 3 Other-like-self and other-unlike-self: the epistemology of subjectivity; CHAPTER 4 Sudden holes'' in time: the epistemology of temporality.
Includes bibliographical references (pages 189-201) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Conrad, Joseph, -- 1857-1924 -- Technique; Conrad, Joseph, -- 1857-1924 -- Technique; Conrad, Joseph, -- 1857-1924; Impressionism in literature; Narration (Rhetoric); Impressionism; Impressionnisme (Littérature); Narration; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Impressionism; Impressionism in literature; Narration (Rhetoric); Technique; Impressionisme; Romans; Engels; Electronic books; Electronic books